5-3(1-9x)=3-2(2x+4)

Simple and best practice solution for 5-3(1-9x)=3-2(2x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(1-9x)=3-2(2x+4) equation:


Simplifying
5 + -3(1 + -9x) = 3 + -2(2x + 4)
5 + (1 * -3 + -9x * -3) = 3 + -2(2x + 4)
5 + (-3 + 27x) = 3 + -2(2x + 4)

Combine like terms: 5 + -3 = 2
2 + 27x = 3 + -2(2x + 4)

Reorder the terms:
2 + 27x = 3 + -2(4 + 2x)
2 + 27x = 3 + (4 * -2 + 2x * -2)
2 + 27x = 3 + (-8 + -4x)

Combine like terms: 3 + -8 = -5
2 + 27x = -5 + -4x

Solving
2 + 27x = -5 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
2 + 27x + 4x = -5 + -4x + 4x

Combine like terms: 27x + 4x = 31x
2 + 31x = -5 + -4x + 4x

Combine like terms: -4x + 4x = 0
2 + 31x = -5 + 0
2 + 31x = -5

Add '-2' to each side of the equation.
2 + -2 + 31x = -5 + -2

Combine like terms: 2 + -2 = 0
0 + 31x = -5 + -2
31x = -5 + -2

Combine like terms: -5 + -2 = -7
31x = -7

Divide each side by '31'.
x = -0.2258064516

Simplifying
x = -0.2258064516

See similar equations:

| 4x-4t=2 | | 16fg-2g= | | s-3t=rt | | A/3-=2 | | t=(t+20)+(t+10) | | -5(1-5x)+5(-8x-2)=-5x-45 | | t=(t+10)+(t+20) | | 65(3h)+130=h | | 5-2(7x+2)= | | 8+5x=9x-8 | | 8+5x=8x-8 | | 6p+10=360 | | 24x-22=-4(1-6k) | | A=9/8(h-75) | | (3+7i)+(4+5i)=0 | | 6x+10=360 | | 0.142857= | | x^2-6x+16=7 | | 7j-10=60 | | (2x-8)^2/3 | | 3(y-5)/4-4y=3(y-3)/2 | | -x+14=-5x+6 | | -7x+16=-3x-16 | | 11x-5=4x+37 | | 4x+19=-2x+61 | | -24=8-(8*r) | | -4x+19=47 | | -4x+11=19 | | -24=8-8r | | 9x+11=2x+74 | | 3a+4b-a-2b= | | f(2)-f(5)=8x-12 |

Equations solver categories